2009
DOI: 10.1017/cbo9780511812163
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear Modeling and Analysis of Solids and Structures

Abstract: This book presents a theoretical treatment of nonlinear behaviour of solids and structures in such a way that it is suitable for numerical computation, typically using the Finite Element Method. Starting out from elementary concepts, the author systematically uses the principle of virtual work, initially illustrated by truss structures, to give a self-contained and rigorous account of the basic methods. The author illustrates the combination of translations and rotations by finite deformation beam theories in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
131
0
13

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 129 publications
(146 citation statements)
references
References 0 publications
2
131
0
13
Order By: Relevance
“…However, due to the applied small displacement beam formulation the results lack in capturing the apparent axial shortening during the acceleration phase, whereas the small elongation due to the centrifugal force in the final near stationary phase is present. The effect of shortening due to bending may be reproduced by a simple post-processing of the results using the beam column theory from [7] as illustrated by a dashed line in Fig. 2 (b).…”
Section: Example: Transient Acceleration Of Prismatic Beammentioning
confidence: 97%
“…However, due to the applied small displacement beam formulation the results lack in capturing the apparent axial shortening during the acceleration phase, whereas the small elongation due to the centrifugal force in the final near stationary phase is present. The effect of shortening due to bending may be reproduced by a simple post-processing of the results using the beam column theory from [7] as illustrated by a dashed line in Fig. 2 (b).…”
Section: Example: Transient Acceleration Of Prismatic Beammentioning
confidence: 97%
“…The simple truss-spring system (Figure 4) was investigated by several authors [28,46,47]. The perfect structure consists of two truss bars in the x − y plane, laterally supported by a horizontal spring in the z direction.…”
Section: Truss-spring Systemmentioning
confidence: 99%
“…Traditional approach of variational formulation of the nonlinear rod deformation problems is to use the variational equation in the form of principle of virtual displacements (Goloskokov, Zhilin), (Elisseev, 1994), (Zhilin, Sergeev, 1994), (Zhilin, et al 1997), (Zhilin, 2007), (Eliseev, Zinov'eva, 2008), (Jelenic, Crisfield, 1999), (Shabana,Yakoub, 2001), (REDDY, 2004), (Antman, 2005), (Gerstmayr, Shabana, 2006), (Shabana, 2008), (Wriggers, 2008), (Krenk, 2009), (Ibrahimbegovic, 2009). In this work, considering the example of plane problem, it is shown that using of the conjugate pairs of strain and stress vectors (Lalin, 2004), the variational problem can be defined as a problem of search for the stationary point of the Lagrangian functional.…”
Section: Introductionmentioning
confidence: 99%